ANGKA BANDING NEUTROFIL/LIMFOSIT DI KARSINOMA PAYUDARA - Yuly Eko Prasetyo; Uleng Bahrun; Ruland DN. Pakasi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Carcinoma Mammae (CM) is a malignancy of epithelial cells restricting at the breast ducts or lobes which causes very high mortalityrate. The Neutrophil/Lymphocyte ratio (NLR) is reflecting the inflamatory status, has been reported to be a prognostic indicator in somemalignant tumors. The purpose of this study is to know the NLR as an indicator of the progressivity of CM by analyzing it. A retrospectiveobservational study performed using data from the medical record of CM patients at Wahidin Sudirohusodo Hospital from January 2010up to December 2012. The diagnosis were established by the clinicians based on the result of histopathological exsamination, chest X-ray,abdominal ultrasound, bone scan and CT scan. The patients with surgical history, chemotherapy, radiotherapy, leukocytes >12.000/mm3and incomplete data were excluded from the analysis. The data distribution was analyzed using Kolmogorov-Smirnov test. The relationbetween NLR in CM was analized by One way ANOVA test and post hoc analysis. The result were 130 samples, consisting of 17 patientsin early stage, 71 in stage III and 42 in stage IV CM. In the early stage the mean of NLR were 1.69, 2.04 in stage III and 2.89 in stage IVand their differences were statistically significant (p<0.001). Post hoc analysis showed that the significant differences occurred betweenthe early stage and IV, as well as between stage III and IV. The mean of NLR were 2.28±1.02 in the non metastatic and 3.36±1.5 in themetastatic they were statistically significant (p<0.001). Based on the study results can be concluded that the neutrophil/lymphocyteratio can be used to assess the progressivity of CM. Further studies with larger samples were needed for the determination of the cut offpoint of NLR.